2001
DOI: 10.1214/aop/1008956698
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Monotonicity and Realizable Monotonicity

Abstract: We explore and relate two notions of monotonicity, stochastic and realizable, for a system of probability measures on a common finite partially ordered set (poset) S when the measures are indexed by another poset A. We give counterexamples to show that the two notions are not always equivalent, but for various large classes of S we also present conditions on the poset A that are necessary and sufficient for equivalence. When A = S, the condition that the cover graph of S have no cycles is necessary and suffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 11 publications
0
51
0
2
Order By: Relevance
“…For those two posets, the algorithm above ensures that G mon = G r.mon holds. Note that this result is known to be false in discrete-time, see for instance examples 1.1 and 4.5 in [FM01].…”
Section: The "Coupling From the Past" Algorithm Revisitedmentioning
confidence: 99%
See 2 more Smart Citations
“…For those two posets, the algorithm above ensures that G mon = G r.mon holds. Note that this result is known to be false in discrete-time, see for instance examples 1.1 and 4.5 in [FM01].…”
Section: The "Coupling From the Past" Algorithm Revisitedmentioning
confidence: 99%
“…We recall that in [FM01] a more general definition of stochastic monotonicity and realizable monotonicity for a system of probability measures is considered: Definition 1.3. Let A and S be two partially ordered sets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather than produce a whole random map which is both monotone and marginalizes to a given Markov chain, it is sufficient to specify how any two given states may be updated together in a monotone fashion. Fill and Machida (1998) show that there are Markov chains with a pairwise monotone update rule but with no monotone randomizing operation, but so far there haven't been any such examples where someone wanted to sample from the steady state distribution.…”
Section: Q: Can You Quantify the User-impatience Bias?mentioning
confidence: 99%
“…It is a common misbelief that, conversely, stochastic monotonicity for K implies realizable monotonicity. This myth is annihilated by Fill and Machida [13] and Machida [30], even for the case of a finite poset X , for which it is shown that every stochastically monotone kernel is realizably monotone (i.e., admits a monotone transition rule) if and only if the cover graph of X (i.e., its Hasse diagram regarded as an undirected graph) is acyclic.…”
Section: Realizable Monotonicitymentioning
confidence: 99%